Keberhasilan Pertautan Sambung Pucuk Beberapa Varietas Mangga (Mangifera Indica) dengan Panjang Entres yang Berbeda - Maulana, Orezae; Rosmaiti, Rosmaiti; Syahri, Muhammad (Agrotekma: Jurnal Agroteknologi dan Ilmu Pertanian, 2020)
This research aims to determine the success of the graft (Mangifera indica) with a variety of mango varieties. This research was conducted in CV. Hutanku District of Birem Bayeun, East Aceh District Aceh Province with a height of place Â± 10 m above. The research was held in Februai until May 2020. The study uses the random Design Group (RAK) factorial pattern consisting of two factors: the firstfactor is the mango plant varieties (V), which consist of 3 levels namely: V1: Arumanis, V2: Manalagi, V3: Apples. The second factor is the long entres Mango Plant (P), which consists of 3 levels namely: P1: Length of entres 10 cm, P2: Length of Entres 12.5 cm, P3: Length of entres 15 cm. Thus acquired 9 treatment combinations with 3 repeats, thus obtained 27 units of trial. Each unit of trial consists of 2 plants in the polybag used as sample. The results of the study showed a very real effect of mango varieties on plant life percentage at age 4, 6 and 8 MSG, high shoots at the age of 4, 6 and 8 MSG, Diameter shoots at ages 4, 6 and 8 MSG, the number of leaves aged 4, 6 and 8 MSG. The best results were obtained in the V1 (Arumanis) treatment. The length ofentres has no noticeable effect on the percentage of life, height buds, diameter buds and the number of leaves at ages 4, 6 and 8 MSG. The interaction between the varietal and long entres has no noticeable effect on the percentage of life, height buds, diameter buds and the number of leaves at ages 4, 6 and 8 MSG.